Jasmonic Acid Impairs Arabidopsis Seedling Salt Stress Tolerance Through MYC2-Mediated Repression of CAT2 Expression - Song, Ru-Feng; Li, Ting-Ting; Liu, Wen-Cheng (Frontiers in Plant Science, 2021)
High salinity causes ionic, osmotic, as well as oxidative stresses to plants, and antioxidant enzyme catalase (CAT) plays a vital role in this process, while how CAT expression is regulated during plant response to high salinity remains elusive. Here. We report that phytohormone jasmonic acid (JA) impairs plant salt stress tolerance by repressing CAT2 expression in a MYC2-dependent manner. Exogenous JA application decreased plant salt stress tolerance while the jar1 mutant with reduced bioactive JA-Ile accumulation showed enhanced salt stress tolerance. JA increased salt-induced H2O2 accumulation, while treatment with H2O2-scavenger glutathione suppressed the effects of JA on plant H2O2 accumulation and salt stress tolerance. JA repressed CAT2 expression in salt-stressed wild-type plant but not in myc2, a mutant of the master transcriptional factor in JA signaling, MYC2, therefore the myc2 mutant had higher salt stress tolerance. Further study showed that mutation of CAT2 largely reverted the lower ROS accumulation, higher catalase activity and enhanced salt stress tolerance of the myc2 mutant in myc2 cat2-1 double mutant, revealing that CAT2 functions downstream of JA-MYC2 module in plant response to high salinity stress. Together, our study reveals that JA impairs Arabidopsis seedling salt stress tolerance through MYC2-mediated repression of CAT2 expression.